2022
DOI: 10.1021/acsphotonics.2c00039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Noise and Background on Measurement Uncertainties in Luminescence Thermometry

Abstract: Materials with temperature-dependent luminescence can be used as local thermometers when incorporated in, for example, a biological environment or chemical reactor. Researchers have continuously developed new materials aiming for the highest sensitivity of luminescence to temperature. Although the comparison of luminescent materials based on their temperature sensitivity is convenient, this parameter gives an incomplete description of the potential performance of the materials in applications. Here, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…It should be noted, however, that it is the interplay between the relative sensitivity and high signal-to-noise ratio that defines the practically actually relevant quantity of statistical precision of a luminescent thermometer. 13,58,59 The statistically expected relative temperature uncertainty is given bywith R 21 ( T ) and S r ( T ) as given in eqn (4) and (5), respectively. Formula (6) is valid under the assumption of Poissonian photon counting statistics of the photodetector, which is given for a photomultiplier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that it is the interplay between the relative sensitivity and high signal-to-noise ratio that defines the practically actually relevant quantity of statistical precision of a luminescent thermometer. 13,58,59 The statistically expected relative temperature uncertainty is given bywith R 21 ( T ) and S r ( T ) as given in eqn (4) and (5), respectively. Formula (6) is valid under the assumption of Poissonian photon counting statistics of the photodetector, which is given for a photomultiplier.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted, however, that it is the interplay between the relative sensitivity and high signal-tonoise ratio that defines the practically actually relevant quantity of statistical precision of a luminescent thermometer. 13,58,59 The statistically expected relative temperature uncertainty is given by…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, photon extinction by biological tissues strongly reduces both the number of excitation photons reaching the luminescent probe (nanoparticle) and the number of emitted photons collected by the detection systems 41 . Swieten et al have demonstrated that when working in conditions of low signal-to-noise ratio, the thermal uncertainty is affected and the performance of the thermometer is compromised 42 . It is therefore desirable to improve the quality of the thermal readout in such circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…The reason behind the low uncertainties in temperature measurements using this probe is that both emissions utilised for LIR have high intensities. Swieten et al 60 recently demonstrated that signal strength is directly proportional to the precision of the temperature measurement. As already mentioned, Cr 3+ emission in the strong crystal field is comprised of the 4 T 2 and 2 E bands, with opposite trends with change in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Swieten at al. 45 recently demonstrated that signal strength is directly proportional to the precision of the temperature measurement. As already mentioned, Cr 3+ emission in the strong crystal field is comprised of the 4 T2 and 2 E bands, with opposite trends with change in temperature.…”
Section: δ𝑇 =mentioning
confidence: 99%